Corrupt Practice of Legal Persons as a Factor Restraining the Development of Russia - CHEBUNINA, Julia Pavlovna (Journal of Advanced Research in Law and Economics; Vol 7 No 6 (2016): Vol 7, No 6(2016): JARLE, Volume VII, Issue 6(20), Fall 2016, 2017)
The paper considers necessity to perfect the current law of the Russian Federation with respect to legal persons committing crimes in economy. Evidence of corrupt practice of legal persons utilizing budgetary funds are given. The objective side of such crimes is represented by inappropriate utilization of the federal budget on an especially large scale. At that, criminality has a dual character. On the one hand, the subjects of such crimes are the state or municipal structures possessing the corresponding finances. On the other hand, there are legal entities of private law taking advantage of the legal uncontrolled from the side of the state and liberality of the current law. The recognition of the status of a legal person as a subject of crimes injurious to the public provides a basis for solving the problem. Russian legislation must be reduced to the international norms, protection of the constitutional order of the state, the economy of which is shaped by legal persons. The laws must adequately correspond to the criminological situations, take into account the foreign experience, contribute to the active counteraction to formation of criminal communities, elimination of discrepancies in legal norms of the Russian Federation administrative and criminal law.
Keywords: crimes of legal persons, consequences of corrupt practice, budgetary funds, criminal and administrative law